2006
DOI: 10.1111/j.1365-2435.2006.01206.x
|View full text |Cite
|
Sign up to set email alerts
|

Forage fermentation patterns and their implications for herbivore ingesta retention times

Abstract: Summary1. Differences in digestive physiology between browsing and grazing ruminant feeding types have been discussed extensively. The potentially underlying differences in fermentative behaviour of forage plants have received much less attention. 2. In this study, different groups of temperate forage plants (grasses, browse leaves and twigs, herbs and legumes) were compared in their chemical composition and fermentative behaviour. They were evaluated via an in vitro fermentation system (modified Hohenheim gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
127
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(138 citation statements)
references
References 114 publications
(131 reference statements)
7
127
0
1
Order By: Relevance
“…Although it is generally accepted that the fermentation rate of browse is faster than it is of grass (du Toit and Yetman 2005; Hummel et al, 2006) because of the differences in insoluble fibre content, the rate of VFA production from DM in giraffes is similar to that of other wild ruminants including grazers Gordon and Illius, 1994). Reduction in particle size by rumination in giraffes to increase digestibility occupies a relatively short part of their day: they allocate a disproportionate time to feeding compared to rumination (du Toit and Yetman 2005), which implies that the size of the particles that enter the rumen stimulate the rumination reflex relatively infrequently.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is generally accepted that the fermentation rate of browse is faster than it is of grass (du Toit and Yetman 2005; Hummel et al, 2006) because of the differences in insoluble fibre content, the rate of VFA production from DM in giraffes is similar to that of other wild ruminants including grazers Gordon and Illius, 1994). Reduction in particle size by rumination in giraffes to increase digestibility occupies a relatively short part of their day: they allocate a disproportionate time to feeding compared to rumination (du Toit and Yetman 2005), which implies that the size of the particles that enter the rumen stimulate the rumination reflex relatively infrequently.…”
Section: Discussionmentioning
confidence: 99%
“…Grass should yield more energy from fermentation per unit forage (Codron et al 2007a), which explains why both in vivo and in vitro overall digestibility (generally measured as digestibility after fermentation times >24 h) are often found to be higher in grass than in woody browse (Wofford and Holechek 1982;Wilman and Riley 1993;Van Wieren 1996b;Hummel et al 2006). However, the evidence is equivocal, as some other references give higher digestibilities for woody browse than for grass (Short et al 1974;Blair et al 1977;Holechek et al 2004).…”
Section: Digestion/fermentation Characteristicsmentioning
confidence: 99%
“…Grass contains more fibre, and a greater proportion of this fibre is cellulose, while browse has less total but more lignified fibre (Short et al 1974;Oldemeyer et al 1977;Owen-Smith 1982;McDowell et al 1983; Cork and Foley 1991;Robbins 1993; Van Wieren 1996b;Iason and Van Wieren 1999;Holechek et al 2004;Hummel et al 2006; Codron et al 2007a). These differences are more pronounced if C4 grasses are compared to browse (Caswell et al 1973).…”
Section: Grass and Browsementioning
confidence: 99%
“…Various authors suggested that the method of microhistological analyses of faeces has limitations to determine ungulate diet compositions, as differential digestion may result in differences between what is ingested and what is excreted (Leslie et al 1983;Mukhtar and Hansen 1983;Barker 1986). Shorter ingesta retention times and slow plant fermentation rates such as for grasses (Clauss et al 2005;Hummel et al 2006) might create a bias in the estimation of the diet composition. No correction for digestibility, however, was necessary as plant cuticle, which is used in this study for plant identification, is indigestible in any animal's guts (Stace 1965).…”
Section: Diet Composition: Backtracking and Faecal Analysismentioning
confidence: 99%